Improvement of In vitro release of Glibenclamide using Cyclodextrin inclusion complexation - Prasad, Neelkant; Garud, Navneet; Garud, Akanksha (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The present study aimed to improve the aqueous solubility of the oral hypoglycemic agent, glibenclamide (GLI), so as to improve its oral absorption, and hence bioavailability after oral administration. This was accomplished by complex formation between GLI and ?-cyclodextrin (?-CD). The study involves the preparation of the inclusion complexes using different techniques. Differential Scanning Calorimetry (DSC) and XRay Diffractometry (XRD) results confirmed the complex formation between GLI and ?-CD. The solubility increase of GLI was due to 1:1 complex formation. The dissolution rate of GLI from the complex prepared by neutralization method was more rapid as compared to other methods used. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21855 Dhaka Univ. J. Pharm. Sci. 13(1): 15-21, 2014 (June)